INTERACTION BETWEEN FINANCIAL SECTOR DEVELOPMENT AND MICROFINANCE INSTITUTION (MFIs) PERFORMANCE IN SOUTHEAST ASIA - Chaerani Nisa; Tia Ichwani; Nurwidhi Arief Sutoyo (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2021)
Abstract: This study aims to examine the effect of financial sector development on the financial and social performance of MFIs. This research is a quantitative research. The population is all MFIs listed on MixMarket. This study uses purposive sampling with MFI criteria that have complete data needed from 1999 to 2019. This study uses panel data because it uses MFIs from nine countries but in different years. Data collected using data from MixMarket with a research period between 1999 and 2019. The results show that the revival of the financial sector has a negative impact on the independence of MFIs. On the other hand, progress in the financial sector also has a negative impact on MFIs for the poor. This condition indicates that there is competition between the two, as developments in the financial sector have a negative impact on the MFI's ability to generate higher incomes. The implication of this finding is that policy makers are more careful in determining the operational reach of the traditional financial sector and MFIs.Abstrak: Penelitian ini bertujuan untuk menguji pengaruh pengembangan sektor keuangan terhadap kinerja keuangan dan sosial LKM. Penelitian ini adalah penelitian kuantitatif. Populasinya adalah semua LKM yang terdaftar di MixMarket. Penelitian ini menggunakan purposive sampling dengan kriteria LKM yang memiliki kelengkapan data yang dibutuhkan dari tahun 1999 hingga 2019. Penelitian ini menggunakan data panel yang karena menggunakan LKM dari sembilan negara tetapi berbeda tahun. Data penelitian dikumpulkan dengan menggunakan data dari MixMarket dengan periode penelitian antara 1999 hingga 2019. Hasil penelitian menunjukkan bahwa kebangkitan sektor keuangan berdampak negatif terhadap independensi LKM. Di sisi lain, kemajuan sektor keuangan juga berdampak negatif pada jangkauan LKM kepada masyarakat miskin. Kondisi ini menunjukkan adanya persaingan di antara keduanya, karena perkembangan sektor keuangan berdampak negatif pada kemampuan LKM untuk menghasilkan pendapatan yang lebih tinggi. Implikasi dari temuan ini adalah pembuat kebijakan lebih berhati-hati dalam menentukan jangkauan operasional sektor keuangan tradisional dan LKM.